Analisis Minat Ibu Hamil Dengan Pemeriksaan Triple Eliminasi Di Puskesmas Panongan : Analysis of Interest in Pregnant Women with Triple Elimination Examination at the Panongan Health Center - Nuraeni; Mariyani (Dohara POAJ, 2023)
Introduction: 6.81% of the Panongan Health Center participated in the Triple Elimination screening. Several factors related to the triple elimination examination include knowledge, sources of information, family support, and support from health workers. Purpose: Knowing the analysis of pregnant women's interests with a triple elimination examination at the Panongan Health Center, Panongan District, Tangerang Regency in 2022. Methods: Quantitative analytic cross-sectional design. The sample of pregnant women who carried out the examination was 63 respondents using an accidental sampling technique. Data were analyzed using the chi-square test. Results: The relationship between knowledge (0,004); sources of information (0,022); family support (0,000); and support from health workers (0,005) with the interest of pregnant women to do triple elimination examination. There is a relationship between knowledge, sources of information, family support, and support from health workers with the interest of pregnant women in carrying out triple elimination examinations. Discussion: The knowledge, sources of information, family support, and health workers are related to the interest of pregnant women to do triple elimination examinations.